Assessing autonomous motivation in students with cognitive impairment*. Issue Volume 39:Issue4(2014) (2nd October 2014) - Katz, Idit; Cohen, Rinat
Abstract: Background Applying Benson's program of validation (Benson, 1998 ) we provide evidence supporting the validity of a projective instrument that assesses the autonomous motivation of students with impaired cognitive abilities. Method Eighty-eight grade 7–9 students diagnosed with cognitive impairment participated in this study. Participants' motivation was assessed using a projective instrument. Participants' affect, task value, and perception of the teachers as supportive were also assessed. The questionnaires were applied individually. Zero order correlation and regression analysis were conducted. Results The study demonstrated internal relations among the observed elements of the projective instrument, as well as relations between the projective instrument with other constructs and the predictive validity of the instrument. Conclusions The evidence provided herein suggests that the projective instrument can be used to validly measure the autonomous motivation of students with cognitive impairment.